ENVIRONMENTAL AND SOCIAL RISKS IN INTERNATIONAL AND DOMESTIC SYSTEMS OF MINERAL RESOURCE ASSESSMENT - Vyzhva, S.; Kurylo, М.; Payuk, S.; Тkachenko, Y. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It was defined that the ecological and social risks became key in the implementation of mining projects from the stage of geological study through development till mining operation. The main components of these risks are fixed over the past years, which are related to the problems of water resources management, the processes of decarbonization of production, the reduction of the negative impact on climate change, the environmental friendliness of production and the emissions volumes that are directly or indirectly related to mining enterprises, etc. A comparison of domestic and international standards for the assessment of mineral reserves and resources was carried out according to the basic features of classification with the determination of social and environmental assessment factors. The features of the Classification of Mineral Reserves and Resources of the State Subsoil Fund, the UN Framework Classification, the PRMS Petroleum Resources Management System, the International Reporting Standards of the CRIRSCO Mineral Resources Committee are analyzed and compared in order to find features that allow determining the social and environmental risks of mining projects. The presence of these direct features in the classification systems indicates the orientation of the assessment standards to the comprehensive assessment of projects as such meeting the goals of sustainable development.The social and ecological viability of subsurface and natural resource projects is used as a direct feature only in the UN Framework Classification, while its inclusion took place in 2009 in the part of social factors, and in 2019 – in the part of environmental factors. This classification is considered as a tool for the effective management of national resources, necessary for the realization of the goals of sustainable development, which enables all stakeholders to find a common understanding of the development of resources and territories, to compare projects in different types of resources and subsoil use. In other international standards, as well as in the domestic classification of the State Fund of Subsoil, socio-ecological criteria are taken into account indirectly, which is one of the key areas of development of these mineral resource assessment systems. Such development can take place in two directions: the inclusion of social and ecological criteria directly as basic features, while this is possible both in the form of complex parameters and individual classes/subclasses; use and improvement of existing methods of resource and reserves valuation, taking into account the environmental and social risks of the implementation of subsoil use projects.
Keywords: nternational standards; eserves assessment; environmental and social risks; features of classification; mineral resources; exploration; mining projects